Sprint interval exercise for fat loss: Good return on investment - Koziris, L. P. (Strength and Conditioning Journal, 2013)
This study showed that an all-out interval exercise protocol resulted in 24-hour oxygen use and, therefore, caloric expenditure equal to that of continuous exercise. The results support repeat sprint exercise as a viable fat loss option, especially fitting for 'power endurance' training needs. Shorter in duration, it can also save training time for fitness clients.